Exercise Fat Oxidation Is Positively Associated with Body Fatness in Men with Obesity: Defying the Metabolic Flexibility Paradigm - Ramos Jimenez, Arnulfo (2021)
Obesity is thought to be associated with a reduced capacity to increase fat oxidation in response to physical exercise; however, scientific evidence supporting this paradigm remains scarce. This study aimed to determine the interrelationship of different submaximal exercise metabolic flexibility (Metflex) markers and define its association with body fatness on subjects with obesity. Twenty-one male subjects with obesity performed a graded-intensity exercise protocol (Test 1) during which cardiorespiratory fitness (CRF), maximal fat oxidation (MFO) and its corresponding exercise intensity (FATmax) were recorded. A week afterward, each subject performed a 60-min walk (treadmill) at FATmax (Test 2), and the resulting fat oxidation area under the curve (TFO) and maximum respiratory exchange ratio (RERpeak) were recorded. Blood lactate (LAb) levels was measured during both exercise protocols. Linear regression analysis was used to study the interrelationship of exercise Metflex markers. Pearson’s correlation was used to evaluate all possible linear relationships between Metflex and anthropometric measurement, controlling for CRF). The MFO explained 38% and 46% of RERpeak and TFO’s associated variance (p < 0.01) while TFO and RERpeak were inversely related (R2 = 0.54, p < 0.01). Body fatness positively correlated with MFO (r = 0.64, p < 0.01) and TFO (r = 0.63, p < 0.01) but inversely related with RERpeak (r = −0.67, p < 0.01). This study shows that MFO and RERpeak are valid indicators of TFO during steady-state exercise at FATmax. The fat oxidation capacity is directly associated with body fatness in males with obesit